Observation of ultrastructure of colored cotton fiber - LI Yue-you; WANG Xue-de (浙江大学学报. 农业与生命科学版)
Electron microscopic examination of white, brown and green fiber revealed that each of these three types of fiber cells was composed of primary wall, secondary wall and lumen from outside to inside. The white fiber cell hadn't been found any deep dyed matter in wall and lumen. The green fiber cell had numerous concentric osmiophilic rings around the lumen, whereas white and brown fibers had no these rings. It was supposed that these rings be formed day by day during green pigment deposition. The brown fiber cell not only had a large lumen deposited by plenty of deep dyed substance, but also had a fork structure which grew up to a branch from the main lumen of fiber cell. After measured the quality of colored fiber, it was very unluckily that the colored fibers had comparatively poorer quality than the whiter fiber, which might be related to lower cellulose content and pigment matter accumulation in colored fibers.